Antidiabetic Property of Muntingia calabura: A Review - Tavamani Balan; Fathiah Husna Rosman; Laavanya Rajendhiran; Nur Ainina Hani Ghazali; Suganya Murugesu; Sharon Fatinathan; Zainul Amiruddin Zakaria; Charles Gnanaraj; Vikneswari Perumal (Asian Journal of Medicine & Health Sciences, 2023)
Muntingia calabura (M. calabura) plant is known to possess various medicinal values, and numerous scientific studies have supported its pharmacological properties. It has been extensively documented that M. calabura has antidiabetic properties. Therefore, this review aims to gather all information related to the antidiabetic activity of M. calabura and present it as a comprehensive review article. Literature has been retrieved from several databases, such as Google Scholar, Research Gate, Wiley, Science Direct, National Center for Biotechnology Information (NCBI), Pubmed, and Springer Link. In this review, several papers will be referred to, including in vitro studies (⍺-glucosidase, ⍺-amylase and dipeptidyl peptidase-IV (DPP-IV)), in vivo studies (animal induced with streptozotocin (STZ) and alloxan), and studies on bioactive compounds of the M. calabura plant. From the review, M. calabura extracts were reported to have a significant effect on antidiabetic activity due to the presence of compounds with high antioxidant activity, such as flavonoids and phenolic acids. Furthermore, the bioactive compounds that possess significant antidiabetic activity were identified. Hence, this plant was concluded to have an important role in future drug development for antidiabetic purposes, and future studies by other researchers can be more accessible by referring to this presented review paper.